Building AI Literacy in Pre-Service Teacher Education in Canada: A Case Study of Two Cohorts - Estaiteyeh, Mohammed; Mindzak, Michael (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
Preparing new teachers for the reality of artificial intelligence in education (AIEd) has become a pressing issue. This study was conducted in a Canadian teacher education program that offers a course on digital technologies incorporating a module on AIEd. This paper addresses two research questions: 1) What were teacher candidates’ (TCs’) experiences with the module on AIEd? and 2) What were TCs’ views on the use of AI by themselves and their students? The study employed an explanatory mixed methods design, combining quantitative and qualitative data gathered via a survey administered to TCs directly following their module completion. Participants were two cohorts of TCs (108 TCs in 2024 and 104 TCs in 2025). Findings show TCs’ satisfaction with the module as they highlighted three major benefits: offering useful teaching resources; more acceptance to explore the technology and embrace it critically; and promoting AI literacy. TCs expressed an inclination to use AI as teachers. However, they expressed negative views toward their students’ use of AI. Additionally, most TCs demonstrated developing levels of critical AI literacy, especially among the most recent cohort. This research offers insights into promoting TCs’ AI literacy and presents implications for teacher education research, practice, and policy.